Value Engineering Model of Hospital Buildings According to Building Technical Standards in Indonesia - Riyanto, Joko; Wahyudi, Slamet Imam; Wibowo, Kartono (Universitas Ibn Khaldun Bogor, 2025)
This study develops a Value Engineering model for hospital buildings that is in accordance with the rules of building technical standards in Indonesia. This standard includes Government Regulation, Regulation of the Minister of Health, and Regulation of the Minister of Public Works and Public Housing. This model aims to, obtain Variable Criteria that meet the requirements of Design eligibility, obtain Solution Strategies for fixing Variables that are less qualified to produce design recommendations with the lowest cost or net and highest benefits, and Provide a Value Engineering model that can be used to assess Design Feasibility, Variables that meet and do not meet the requirements, Strategies for fixing less qualified variables, Strategies for obtaining Design Recommendations at the lowest price or net benefit as high as possible. The results of the model can be applied to the design phase in planning. This Value Engineering Model is an Abstract Development of a soft system model with DSS (Decision Support System).